Screen printed bifunctional gas diffusion electrodes for aqueous metal-air batteries: Combining the best of the catalyst and binder world - Flegler, Andreas; Hartmann, Sarah; Settelein, Jochen; Mandel, Karl; Sextl, Gerhard (Electrochimica Acta, 2017)
The oxygen reactions in a metal-air battery during discharge (oxygen reduction reaction: ORR) and charge (oxygen evolution reaction: OER) take place on accessible catalyst sites at the gas diffusion electrode (GDE or air-cathode). Typical low-cost catalysts only have function for either the ORR (e.g. MnO2) or the OER (e.g. NiCo2O4). To overcome this issue, either a bifunctional catalyst or a bifunctional GDE is needed. Herein, we focus on the development of such a bifunctional GDE. One key is the use of a carefully tuned binder which allows optimal wetting of the GDE. The combination of carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) can replace conventional binders such as polytetrafluoroethylene (PTFE). Using this binder system, two different approaches to combine the two catalysts γ-MnO2 and NiCo2O4 in one cathode are employed. The first is to mix the ORR catalyst γ-MnO2 and the OER catalyst NiCo2O4 for integration in the same reactive layer. The second is to build a GDE with two reactive layers which are screen printed on top of each other. The reactive layer facing the air side consists of the ORR catalyst γ-MnO2 and the binders CMC/SBR. The second reactive layer, facing the electrolyte, consists of the hydrophilic binder CMC and the OER catalyst NiCo2O4. This double-layer design with two different catalyst species results in a better cycling behavior.
CRIS-Team Scopus Importer:2020-04-02
Keywords: Bifunctional air-cathode; Bifunctional gas diffusion electrode; Hydrophilic and hydrophobic reactive layer; Screen printing